Changes of glaciers in the Karakoram Region and of ice shelves on the Antarctic Peninsula – Results from a multi-mission satellite image analysis - Rankl, Melanie (2016)
The components of the cryosphere are sensitive indicators of past and present climate variability. They provide some of the most detectable evidence of global climate change. The contribution of ice sheets, glaciers and ice caps to global sea-level rise has considerably increased during recent decades. Hence, the monitoring of these components on a regular basis is of great importance. The repeat observations and measurements of cryospheric variables have become available with the launch of Earth Observation satellites. These instruments are very suitable to monitor large-scale changes on repeat intervals due to wide footprints and both high spatial and temporal resolution. Above all, active remote sensing systems operating in the microwave domain of the electromagnetic spectrum were most useful. These systems work independently from daylight since they provide their own source of radiation and are able to penetrate through clouds or dust. Modern twin satellite missions, such as the TanDEM-X mission, offer new possibilities for interferometric processing due to very short temporal baselines between image acquisitions. The goal of this study was to investigate the potential of new satellite mission data in conjunction with archived data for the quantification of changes of the cryosphere. For this purpose, glaciers in a high mountain area and floating ice shelves on the margin of the Antarctic ice sheet were selected. The respective cryospheric variables showed highly dynamic behavior during the last decades and were hence, chosen for this study. Several remote-sensing based methods were used and adapted to specific requirements of the satellite data or the studied objects. The applied methods include: the use of multi-spectral satellite data for mapping glacier outlines and termini position changes, the monitoring of changes in glacier surface flow by means of ‘intensity offset tracking’ algorithms and the quantification of glacier elevation and mass changes using SAR interferometry. In order to monitor ice ...